Analisis Bisnis Konter Pulsa pada Aspek Perilaku Konsumen : Studi Kasus Saadah Cell - Ramanda Gunawan; Hani Humaeriyah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The development of digital technology has made mobile credit and digital transaction services primary needs of society. This condition creates significant business opportunities for mobile credit outlets, accompanied by intense competition. This study aims to analyze the business feasibility of Saadah Cell mobile credit outlet based on consumer perceptions and supporting business aspects. The research employed a descriptive qualitative method with data collected through a survey of 30 respondents who were customers of the outlet in 2026. The results indicate that most consumers gave positive assessments of product and service quality, transaction speed and convenience, system security, and friendly customer service. In terms of pricing, consumers perceived the prices as affordable, competitive, and proportional to the service quality received. Purchasing decisions were strongly influenced by customer satisfaction and trust, leading to repeat purchases and recommendations. Furthermore, analysis of market and marketing aspects, human resources, economic and socio-cultural factors, technical and technological readiness, financial feasibility, and risk management shows that the mobile credit outlet has stable profit potential, good operational readiness, and manageable business risks. Therefore, Saadah Cell mobile credit outlet is considered feasible and sustainable for further development.